A COMPARITIVE EVALUATION OF SPECIES OF GUDUCHI (TINOSPORA CORDIFOLIA (WILID.) MEIRS EX HOOK. F & THOMS., TINOSPORA MALABARICA MEIRS EX HOOK, TINOSPORA CRISPA MEIRS.) W.R.T SATWA - Anjana J*; Seema Pradeep; Shiva Manjunatha M.P; Anjali Asok; Akshatha M Bhat (AYUSHDHARA, 2018)
Background: Guduchi is a plant belonging to Menispermaceae family and widely used in Ayurvedic system of medicine. Tinospora cordifolia is the accepted botanical source of Guduchi. All the three species are indigenous to the tropical areas of India, Sri Lanka and Myanmar. Guduchi Satwa is the most commonly used dosage form of the plant for various conditions like fever, arthritis, gastric ulcer cough etc. Tinospora cordifolia (Guduchi) is a widely used shrub in folk and Ayurvedic systems of medicine. Species of the plant, stem size, collection time, season and maturity of the plant may affect the yield and physico-chemical profile of Guduchi Satwa. Due to high demand and less yield of Satwa from Guduchi plant, market sample of Guduchi Satwa is subjected to adulteration. Hence this study is aimed at standardizing Guduchi Satwa prepared from all the three available species of the plant. Methodology: The study deals with preparation of Satwa as per the classical text of Ayurveda, identifying organoleptic features, conducting physicochemical and photochemical screening of the Satwa of all the above mentioned species of Guduchi (Tinospora cordifolia (wilid.) Meirs ex hook. f & thoms., Tinospora malabarica meirs ex hook, Tinospora crispa meirs.). Results: The study provided significant difference in the yield of Satwa. Variations in the organoleptic characters were insignificant. All the phytoconstituents were found to be same and the physicochemical values were within the limits in all three species.